Application and prospect of ROS-related nanomaterials for orthopaedic related diseases treatment - Yang, Wenbo; Zeng, Qianwen; Pan, Qing; Huang, Wei; Hu, Hongzhi; Shao, Zengwu (Frontiers in Chemistry, 2022)
The importance of reactive oxygen species (ROS) in the occurrence and development of orthopaedic related diseases is becoming increasingly prominent. ROS regulation has become a new method to treat orthopaedic related diseases. In recent years, the application of nanomaterials has become a new hope for precision and efficient treatment. However, there is a lack of reviews on ROS-regulated nanomaterials for orthopaedic related diseases. Based on the key significance of nanomaterials for the treatment of orthopaedic related diseases, we searched the latest related studies and reviewed the nanomaterials that regulate ROS in the treatment of orthopaedic related diseases. According to the function of nanomaterials, we describe the scavenging of ROS related nanomaterials and the generation of ROS related nanomaterials. In this review, we closely integrated nanomaterials with the treatment of orthopaedic related diseases such as arthritis, osteoporosis, wound infection and osteosarcoma, etc., and highlighted the advantages and disadvantages of existing nanomaterials. We also looked forward to the design of ROS-regulated nanomaterials for the treatment of orthopaedic related diseases in the future.